RANCANG BANGUN ALAT PENGERING IKAN ASIN EFEK RUMAH KACA BERBENTUK PRISMA SEGI EMPAT UNTUK PEDAGANG IKAN ASIN DI PASAR MODERN BSD - Soewono, Arka D.; Darmawan, Marten; Gunawan, Harjadi (Jurnal Abdimas Bina Bangsa, 2025)
According to the SNI 01-2721-1992 standard, the permissible moisture content for fish is around 40%. However, fresh fish naturally contains more than 40% water. To meet this standard, fish must undergo a drying process. In Indonesia, salted fish is commonly prepared by sun-drying the fish on bamboo mats. However, this method has several drawbacks, such as requiring large areas of land, heavy dependence on weather conditions, long drying times, and the risk of contamination by dust and dirt. One solution that has been developed is an artificial drying method using a greenhouse effect. In this activity, a drying tool shaped like a rectangular prism was designed and equipped with stones at the bottom to store heat and exhaust at the top. This tool was tested by comparing the mass of the fish before and after drying. The results showed that the fish's initial mass of 24.22 grams decreased to 21.28 grams after being dried for 2 days at an average temperature of 36.7°C.